UPDATE OF THE CULTURAL-HISTORICAL POTENTIAL OF POLYVOICES IN CHORAL PERFORMANCE AS AN ENVIRONMENTAL GUIDELINE - Arefieva, Elizaveta (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
The ecological categorical imperative of cultural creation prompts the reflection on the entire corpus of meta-ecological issues in art. The aim of the article is to determine the phenomenon of the ecosystem approach to the actualization of partes singing in modern choral performance. Research methodology is presented with comparative and systematic approaches, which makes it possible to carry out a comparative analysis of monophonic and part singing as sources of modern choral performance. Research results. The ecological categorical imperative of cultural creation prompts us to comprehend the entire body of meta-ecological issues of art. The prefix "meta" presents two dimensions of cultural ecosystems: "post-natural", the actual cultural dimension, and "meta" describes the universal dimension of cultural creation, in particular the paradigm of metaecology as a universal reflective instruction. A wide field of performing paradigms is being formed, which unfold in the space of both self-sufficient artistry, the personification of performing skill, and a large layer of symbiosis of performing skill, which combines the potential of communicative inversions and at the same time a reconstructive space where they try to repeat or simulate the performing skill of local bands. Discussion The actualization of metaphysical origins in art is not a one-dimensional process, it requires polyphonic, polystructural, polycomponent and polykinetic procedural integrity of the modulation of the artistic image. Conclusions. The symbiosis of monophonic and partes singing is implicitly formed as a correlation between the extensive and intensive metrics of sound production. The vertical of the main voice-mode is formed. The musical fabric of the choral performance is transformed, becomes composite. The newest genres of instrumental music are being formed: sonata, symphony, suite, concert